Remembering Imperfectly: Bridging the Past and Future Through Yiddish-American Folk Song Recordings - Levine, Zeke (Schweizer Jahrbuch für Musikwissenschaft, 2026)
In the liner notes for the 1957 Folkways Records release Jewish Children’s Songs and Games ethnomusicologist and performer Ruth Rubin explains, “many Jewish children have grandparents who came from the old country. The Yiddish songs on this record were sung by such grandmothers and grandfathers when they were children in Eastern Europe. When we sing them now, it is as if we were paying a visit to the little town or village where they were born, in the old country.” Rubin’s reflection invites an analysis of the role of Yiddish-American folk song recordings in mediating the music of the Yiddish past for future generations of listeners. I argue that ethnographic recordings and commercially released folk LPs in the mid-twentieth century United States represent the preservationist impulses of the period, which themselves coloured and shaped recorded performances.